Budaya Islam Pesisir; Makna Tradisi Petik Laut bagi Masyarakat Desa Kemantren Lamongan - M Thoriqul Huda Thoriq; Putri Wulandari Putri (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
The Petik laut, a tradition that has taken root in the lives of coastal communities, is not only a symbol of gratitude for the abundant marine products but also a milestone in the continuity of Indonesian culture in the modern era. Amid changing times, this tradition remains an important part of the identity and social life of coastal communities. This research aims to gain a deeper understanding of the significance and dynamics of the petik-laut tradition in the context of the Kemantren Village community, Lamongan. A qualitative method was chosen to investigate the more complex and substantial aspects of this tradition by conducting direct observations in the field to gain a deeper understanding. The research subjects were residents of Kemantren Village, especially those directly involved in fishing activities. Through interviews, observations, and participation in local activities, the researcher attempted to permeate the values, beliefs, and roles attached to the tradition of petik lauts in the community. The results revealed various aspects ranging from the details of the implementation of the tradition to its meaning for various groups in the community, such as religious leaders and the younger generation. In addition, the research also highlights the social function of the petik-laut tradition in strengthening solidarity and maintaining social harmony in the context of community life in Kemantren Village, Lamongan. By better understanding this tradition, it is hoped that it can provide valuable insights to maintain and enrich valuable cultural heritage for future generations.